Cinética de recristalização estática e evolução da textura cristalográfica do aço inoxidável ferrítico 430 estabilizado com nióbio com base na técnica de microscopia por orientação de imagens - Paula Oliveira Malta (2016)
Ferritic stainless steels represent materials with great potential for application in various industrial sectors. The addition of stabilizing elements attribute to steel better weldability and formability. The properties of these materials can also be modified through mechanical and thermal processes. In this context, it is intended to evaluate the microstructure of niobium stabilized ferritic stainless steel AISI 430 and, starting from cold rolling and isothermal annealing analysis the recrystallization kinetics and the evolution of crystallographic texture of the material. Microstructural characterization of the samples was performed using optical, scanning and transmission electron microscopy. The study of this steel recrystallization kinetics was held by the techniques of microhardness measuring and quantitative metallography, as well as through the analysis of KAM and GOS parameters via EBSD. At the end of this study, settled a comparison of the recrystallized fractions and the parameters of JMAK and MPM models obtained for each method. The evaluation of microhardness data proves that the steel softening process advanced according time and annealing temperature. The recrystallization kinetics of both samples series exhibited similar behaviors as regards to quantitation of softening fraction, as well as of recrystallized fraction via quantitative metallography and EBSD analysis. The heat treatment temperature exerted greater influence in softening and recrystallization kinetics in comparison with annealing time. The mean value of activation energy of 430-NR and 430-R series were 428.1 kJ.mol-1 and 359.1 kJ.mol-1, respectively. The steel recrystallization was based in the combination of ON and SG theories, so that the {554}<225> recrystallized grains presented a dimensional advantage compared to others recrystallized grains. The CSL fraction became larger as the temperature increased, indicating that some of this special boundaries were related with the development of recrystallization process. The {554}<225> component, associated with 19a CSL boundary, exerted a marked control in the mechanism of selected growth upon the recrystallization end.